2019
DOI: 10.1111/tra.12704
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular condensates in neurodegeneration and cancer

Abstract: The intracellular environment is partitioned into functionally distinct compartments containing specific sets of molecules and reactions. Biomolecular condensates, also referred to as membrane‐less organelles, are diverse and abundant cellular compartments that lack membranous enclosures. Molecules assemble into condensates by phase separation; multivalent weak interactions drive molecules to separate from their surroundings and concentrate in discrete locations. Biomolecular condensates exist in all eukaryote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 325 publications
(350 reference statements)
0
79
0
Order By: Relevance
“…This hardening of FUS condensates is associated with the formation of supramolecular FUS fibrils that have properties of amyloid-like aggregates. Besides neurodegenerative disorders, current research further suggests emerging roles of aberrant condensates in cancer ( Alberti and Dormann, 2019 ; Spannl et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This hardening of FUS condensates is associated with the formation of supramolecular FUS fibrils that have properties of amyloid-like aggregates. Besides neurodegenerative disorders, current research further suggests emerging roles of aberrant condensates in cancer ( Alberti and Dormann, 2019 ; Spannl et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A literature search to identify protein condensates similar to proSAAS spheres revealed that most aggresomes described to date are nuclear, much smaller (less than one micron), and heterogeneously shaped rather than spherical (reviewed in (Spannl et al, 2019;Wolozin and Ivanov, 2019)). Three nuclear protein condensates do produce membrane-less spherical particles.…”
Section: Discussionmentioning
confidence: 99%
“…While membraneless compartments have important functions in cell (neurons) physiology, they can become pathological when formed on the expression of mutated proteins and/or when cells are exposed to stress. The same review describes how this can lead to abnormal aggregation of granule components, as is observed in pathological contexts, and is thought to underlie the progression of neurodegenerative diseases . Interestingly, aberrant phase separation also seems to occur in cancer as reported in the review from Spannl et al…”
mentioning
confidence: 87%
“…The same review describes how this can lead to abnormal aggregation of granule components, as is observed in pathological contexts, and is thought to underlie the progression of neurodegenerative diseases . Interestingly, aberrant phase separation also seems to occur in cancer as reported in the review from Spannl et al…”
mentioning
confidence: 87%